Sleep Disorder Prevalence among Brazilian Children and Adolescents with Down Syndrome: An Observational Study - Luiza Torres-Nunes; Patrícia Prado da Costa-Borges; Laisa Liane Paineiras-Domingos; José Alexandre Bachur; Danúbia da Cunha de Sá-Caputo; Mario Bernardo-Filho (Applied Sciences, 2023)
Background: Down syndrome (DS) is the most common chromosomal disorder and is related to congenital heart disease, sleep disorders and obesity. Sleep problems are common in DS children, including obstructive sleep apnea. This study aimed to investigate the prevalence of sleep disorders in a group of 41 DS children and adolescents, by two validated questionnaires. Methods: This is a qualitative observational study. The guardians of DS individuals (1–17 years old) answered two questionnaires (sleep questionnaire by Reimão and Lefévre–QRL and sleep disorders scale for children–SDSC) using the Google forms tool. Results: Most DS children wake up at least once during the night (68.28%), sleep during the day (56%) and fall asleep within 15 to 30 min (36.58%), urinate in the sleep at night (53.65%), move around a lot while sleeping at night (78.04) and snore at night (53.66%). In SDSC, 36.59% (n = 15) have some sleep disorder and 29.3% (n = 12) have sleep-disordered breathing. Conclusions: The DS children and adolescents present sleep-compromising factors. Moreover, obstructive sleep apnea is the most prevalent sleep-disordered breathing. Considering the findings of the current study, Google forms is an important tool to evaluate the sleep disorders of DS children and adolescents.